Supramolecular Predisposition Promotes Intramolecular Heavy-Atom Effects for Self-Sensitized Oxidation - Fei Li; Yibin Sun; Guanglu Wu (Journal of the American Chemical Society, 2026)
Abstract Supramolecular confinement is widely used to control molecular architecture, but its use to direct excited-state reaction pathways remains underexplored. This limitation is particularly evident for spin-forbidden processes such as intersystem crossing (ISC), which are difficult to regulate through supramolecular design. The heavy-atom effect, although central to promoting ISC, is typically regarded as an intrinsic substituent property rather than a geometry-dependent supramolecular parameter. Here we show that macrocycle-directed supramolecular predisposition can deliberately enforce intramolecular heavy-atom effects to activate latent spin-forbidden transitions, enabling efficient self-sensitized oxidation. Encapsulation of a flexible aldehyde- and bromine-substituted guest within cucurbit[8]uril (CB[8]) enforces a folded geometry that juxtaposes the heavy atom and reactive aldehyde, as established by solution studies and single-crystal analysis. Under white-light irradiation, this predisposed complex undergoes selective oxidation of the aldehyde to the corresponding carboxylic acid. Control experiments varying heavy-atom identity, cavity size, and guest binding modes define CB[8]-enforced spatial juxtaposition as the critical structural requirement, while scavenger and EPR studies support triplet-oxygen energy transfer to generate singlet oxygen as the operative pathway. Preferential binding of CB[8] to the substrate over the product mitigates product inhibition and allows catalytic turnover under substoichiometric host loadings. These results show that macrocyclic encapsulation does more than statically stabilize a host−guest complex: it transforms spatial geometry into a structurally gated switch for spin-forbidden pathways, establishing supramolecular predisposition as a versatile design principle for developing switchable photocatalysts and conformationally responsive smart materials.